The Relevance of Tarbawi Interpretation in Shaping Students’ Character: A Study of Tafsir Al-Mishbah by M. Quraish Shihab - M. Iqbal Algani; Charles Rangkuti; Hery Iswandi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
A moral crisis occurs when a person loses the attitude, character, and behavior that are in accordance with goodness. Moral and ethical crises often occur among the younger generation in Indonesia due to various factors, such as the impact of globalization, the influence of social media, the lack of parental involvement, and the lack of character education in schools. This study aims to explore the relevance of character education values in M. Quraish Shihab's Tafsir Al-Mishbah to the problems faced by students in the contemporary era. The crisis of morality, bullying, and the threat of radicalism are the background to the urgency of internalizing contextual Qur'anic values. This research is qualitative in nature, using library research, a thematic approach, and content analysis. The results show that the concept of character education in Tafsir Al-Mishbah is rooted in the relationship between the meaning of Rabb and tarbiyah, which aims to shape Insan Kamil through intellectual and spiritual balance. Analysis of Q.S. Luqman: 12-13, Q.S. Al-Hujurat: 11-13, and Q.S. Al-Mujadilah: 11 reveals fundamental values such as monotheism, gratitude, tolerance, and manners in seeking knowledge. The relevance of the findings shows that Quraish Shihab's moderate (wasathiyah) thinking is very effective in protecting students from extreme ideas, building digital literacy ethics through the principle of tabayyun, and eliminating the culture of violence in schools through a humanistic approach. This study concludes that Tafsir Al-Mishbah offers a functional methodological framework for strengthening the character of 21st-century students.